Power, participation and partnerships: reflections on the co-creation of knowledge. Issue 1 (2nd January 2018) - Madsen, Wendy; O'Mullan, Cathy
Abstract: Narrative writing was used to critically reflect on the reasons for the success and failure of two research partnerships: one between the authors and a community group, the other between the authors and academic colleagues. The reflections relate to a vignette constructed on the experiences of the authors and somewhat fictionalised, but brought together to highlight the contrasts, whereby one research partnership was successful in producing outcomes while the other was not. An analysis of these reflections was informed by Wenger's Communities of Practice framework. This helped draw out issues around power and participation as fundamental for successful research partnerships, particularly multidisciplinary partnerships, intent on the co-creation of knowledge. Such issues related to recognising partnerships and the underlying assumptions when these partnerships cross boundaries include transparent communication, power and decision-making processes, critical self-awareness, and negotiated meaning and identity.